(untitled) (Revista de Psicología, 2023)
The Skills and Difficulties Questionnaire (SDQ) is widely used for the assessment of socio-emotional behaviors in children from 4 to 16 years of age. Different structural models have been validated, varying between the number of dimensions, grouping of variables and first and second order factors. The following study seeks to evaluate the psychometric properties of the SDQ through an exploratory and confirmatory factor analysis, in a sample of 330 children between the ages of 2 and 4 who attend care centers in Uruguay. The results show that the original model is the one with the best internal consistency but poor structural fit. The bifactorial model was the one that obtained the best adjustment